Evaluasi Program Pengendalian Hipertensi di Puskesmas Ulee Kareng Kota Banda Aceh Tahun 2022-2024 - Nura Shara Amirza; Nazariah Nazariah; Rina Hasnita; Dharina Baharuddin; Meutia Zahara (Pusat riset dan Inovasi Nasional, 2025)
Hypertension is a non-communicable disease (NCD) with a high prevalence in Indonesia and is a major cause of serious complications, such as stroke, kidney failure, and heart disease. The high incidence of hypertension makes this disease a primary focus of NCD control efforts at the primary healthcare level. The Ulee Kareng Community Health Center has implemented a sustainable hypertension control program for the past three years with the aim of reducing the incidence of complications and improving patients' quality of life. This study aims to evaluate the implementation of the hypertension control program using a logic model framework that encompasses five aspects: input, process, output, outcome, and impact. The research method used is descriptive analytic with a mixed methods approach, combining quantitative and qualitative data to obtain a comprehensive overview of program implementation. The results indicate that the hypertension control program at the Ulee Kareng Community Health Center has had a positive impact. In terms of output and outcome, there has been an increase in patient compliance with therapy prescribed by healthcare professionals, a decrease in blood pressure in the majority of patients, and a decrease in the number of hypertension-related complications. This indicates that the program is quite effective in achieving its intended goals. However, several challenges remain. The main problems lie in the suboptimal data recording system and the suboptimal delivery of health education. To improve the program's effectiveness in the future, recommendations include strengthening the monitoring and evaluation system, increasing the capacity of health workers and cadres through training, and developing innovative media and educational strategies to make information more easily understood and applied by the public.